Objective measurement for surgical skill evaluation - Ahmmad, Siti Nor Zawani (Penerbit UTM Press, 2016)
The purpose of this study was to identify measurable parameters that can be used to quantitatively assess psychomotor skills, specifically for surgical skills assessment. Sixteen participants were recruited from two groups: surgeon (N = 5) and non-surgeon (N = 11). Both groups underwent a psychomotor test using a custom developed ‘Green Target’ module which was designed using a virtual reality system. Six parameters were used to compare the psychomotor skills between the two groups. The results showed that surgeons outperformed the non-surgeons in five out of six parameters investigated and the difference was statistically significant. The average normalised comparison values for surgeons and non-surgeons for motion path accuracy, motion path precision, economy of movement, end-point accuracy and end-point precision were 0.13+0.12 and 0.17+0.12, 0.08+0.11 and 0.10+0.10, 3.76+1.76 and 4.08+2.24, 0.12+0.10 and 0.17+0.11, 0.04+0.10 and 0.07+0.10 respectively, p < 0.05). These parameters can potentially be used to objectively assess the performance of surgical skill.